Cuidados de enfermería en pacientes de posquirúrgico inmediato de amputación del pie diabético: revisión sistemática - Irua Balarezo, Emma Judith (2025)
Introduction: This research addresses nursing care in the immediate postoperative period of patients with diabetic foot amputation highlighting key interventions and best practices based on evidence. Objective: To analyze the current scientific evidence related to nursing care aimed at patients at the immediate postoperative period following a diabetic foot amputation through a systematic review. Methodology: For the purposes of this research, a systematic review was carried out with a qualitative design and a descriptive, exploratory, and cross-sectional type. To identify nursing care directed patients with diabetic foot, scientific evidence was analyzed from the categories that emerge from the systematic review, following the PRISMA methodology guidelines. Results: Uncontrolled diabetes can lead to amputation, the prevalent risk factors found being high blood pressure, smoking, dyslipidemia, and alcoholism. Conclusions: One of the complications in postoperative diabetic foot amputation patients is the amputation itself because of possible neurological and vascular alterations in the lower limbs. The performance in the nursing care process is focused on providing care to the amputated patient according to professional practice to satisfy the needs of the postoperative phase of diabetic foot amputation patient as well as ensuring proper procedures to avoid iatrogenesis.